Zastosowanie modelu regresji liniowej w analizie kapitału obrotowego w małych i średnich przedsiębiorstwach - Bartoszewicz, Bartłomiej; Garbicz, Bartłomiej (Application of Regression Models to Working Capital Analysis in Small and Medium Firm Sector, 2007)
Analysis of accounts receivable and accounts payable is an important part of working capital management. In this paper a regression model of accounts receivable and accounts payable is presented. The research hypothesis is that these quantities (for a company in small and medium firm sector) not only depend on income and costs, but also on factors external to the enterprise, such as financial situation of suppliers and clients, and the entire economy (quantified by indicators published by the Central Statistical Office).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 158-165